[Top][All Lists]

[Date Prev][Date Next][Thread Prev][Thread Next][Date Index][Thread Index]

[potluck dish] Extremely simple Recursive Descent Parser

From: Panicz Maciej Godek
Subject: [potluck dish] Extremely simple Recursive Descent Parser
Date: Tue, 16 Feb 2016 00:28:23 +0100

Sorry that I didn't have time to prepare anything better, but here's a little appetizer.
It is my implementation of recursive descent parser. Perhaps it isn't as expressive as bison or yacc, but it is considerably shorter :)

It implements backtracking through the mechanism of exceptions. The code is so small that I'm pasting it here, along with example usages. It uses the srfi-1 module as well as my (ice-9 nice-9) module to annoy Taylan a little ;]

Here it is:

(use-modules (srfi srfi-1) (ice-9 nice-9))

(define ((in? l) x)
  (match l
    ((h . t)
     (or (eq? x h)
         ((in? t) x)))

(define (non-terminals grammar)
   (map (λ ((non-terminal => . production))

(define (terminals grammar)
  (let ((non-terminals (non-terminals grammar))
        (productions (append-map (λ ((non-terminal => . production))
    (delete-duplicates (lset-difference eq? productions non-terminals))))

(define ((recursive-descent-parser grammar) input)
  (let ((non-terminals (non-terminals grammar))
        (terminals (terminals grammar))
        (((initial-rule => . _) . _) grammar))
    (define (initial-match? rule input)
      (let* ((prefix _ (span (in? terminals) rule))
             (prefix-length (length prefix)))
        (and (>= (length input) prefix-length)
             (equal? prefix (take input prefix-length)))))

    (define (match-rule rule input)
      (match rule

        (((? (in? terminals) t) . next)
         (let (((token . input) input))
           (if (eq? token t)
               (let ((rest input (match-rule next input)))
                  `(,token . ,rest)
               (throw 'parse-error input))))

        (((? (in? non-terminals) A) . next)
         (let* ((parsed input (parse-rule A input))
                (rest input (match-rule next input)))
            `(,parsed . ,rest)

    (define (parse-rule rule-name input)
      (let try ((variants (filter (λ ((name => . rule))
                                    (and (eq? name rule-name)
                                         (initial-match? rule input)))
        (catch 'parse-error
          (λ ()
            (match variants
              (((A => . first-rule) . _)
               (let ((parsed input (match-rule first-rule input)))
                  `(,A . ,parsed)
               (throw 'parse-error input))))
          (λ errors
            (match variants
              ((failed . remaining)
               (try remaining))
               (throw 'parse-error input)))))))
    (parse-rule initial-rule input)))

;; for example:
((recursive-descent-parser '((A => a A b)
                             (A => c)))
 '(a a a c b b b))
;; => (A a (A a (A a (A c) b) b) b)

((recursive-descent-parser '((<S> => a <S> d)
                             (<S> => <B>)
                             (<B> => b <B> c)
                             (<B> => e)))
 '(a a b b e c c d d))
; => (<S> a (<S> a (<S> (<B> b (<B> b (<B> e) c) c)) d) d)

((recursive-descent-parser '((<S> => <A> <B>)
                             (<A> => a <A>)
                             (<A> => x)
                             (<B> => b <B>)
                             (<B> => x)))
 '(a a a a x b b x))
; => (<S> (<A> a (<A> a (<A> a (<A> a (<A> x))))) (<B> b (<B> b (<B> x))))                                     

;; note that the parser doesn''t always work;
;; it only works for the so-called LL grammars
;; for instance, the following grammar will result
;; in stack overflow:

((recursive-descent-parser '((<A> => <A> + <B>)
                             (<A> => <B>)
                             (<B> => a)
                             (<B> => c)))
 '(a + c + a + c + a + a))

;; ~~~> <boom!>

;; However, the grammar can be transformed to an equivalent form:

((recursive-descent-parser '((<A> => <B> +<B>*)
                             (+<B>* => + <B> +<B>*)
                             (+<B>* => )
                             (<B> => a)
                             (<B> => c)))
 '(a + c + a + c + a + a))

;; but then, some strange non-terminal symbols appear:
;=> (<A> (<B> a) (+<B>* + (<B> c)
;             (+<B>* + (<B> a) (+<B>* + (<B> c)
;             (+<B>* + (<B> a)
;             (+<B>* + (<B> a) (+<B>*)))))))

; We need to introduce additional transformation on the ouput:

(define (eliminate+<B>* tree)
  (match tree
    (('<A> <B> +<B>*)
     `(<A> ,<B> . ,(eliminate+<B>* +<B>*)))

    (('+<B>* '+ <B> +<B>*)
     `(+ ,<B> . ,(eliminate+<B>* +<B>*)))



 ((recursive-descent-parser '((<A> => <B> +<B>*)
                              (+<B>* => + <B> +<B>*)
                              (+<B>* => )
                              (<B> => a)
                              (<B> => c)))
  '(a + c + a + c + a + a)))

;=> (<A> (<B> a) + (<B> c) + (<B> a) + (<B> c) + (<B> a) + (<B> a))                                            

Happy birthday, Guile!

reply via email to

[Prev in Thread] Current Thread [Next in Thread]